Analysis Of Factors Affecting The Exchange Value Of Farmers In The Food Corp Subsector In Lampung Province - Wulan Dwi Lestari; Dedy Yuliawan (CV. ITTC INDONESIA, 2026)
Farmers’ welfare remains a major issue in agricultural development, particularly in Lampung Province, Indonesia, where agriculture is a primary source of rural income. Despite increasing rice production, improvements in farmers’ welfare are often constrained by fluctuations in commodity prices, production costs, and inflation. This study aims to analyze the effects of rice production and inflation on the Farmer’s Terms of Trade (NTP) in the food crops subsector in Lampung Province in both the short and long term. A quantitative approach was employed using monthly time-series data from 2021–2025. Secondary data on rice production, inflation, and Farmer’s Terms of Trade were obtained from the Central Statistics Agency (BPS) and the Ministry of Agriculture. The Autoregressive Distributed Lag (ARDL) model was applied to examine short-run dynamics and long-run relationships among variables. The results indicate that, in the short term, rice production has a negative and significant effect on the Farmer’s Terms of Trade, while inflation has a positive and significant effect in several lag periods. In the long term, rice production positively and significantly affects the Farmer’s Terms of Trade, whereas inflation has a negative and significant effect. The Error Correction Term (ECT) confirms a stable long-run equilibrium relationship among the variables. These findings imply that improving farmers’ welfare requires not only increased agricultural productivity but also stable inflation to maintain farmers’ purchasing power and support sustainable agricultural development.